Unravelling the prebiotic origins of the simplest α-ketoacids in cometary ices: a computational investigation - Dash, Soumya Ranjan; Pandya, Rinu; Singh, Geetika; Sharma, Himanshu; Das, Tamal; Haldar, Hritwik; Hotha, Srinivas; Vanka, Kumar (CHEMICAL COMMUNICATIONS, 2024)
Keywords: GLYOXYLATE; Hydrocarbons; Metabolism; Precursors

Hypersilylsilylene-supported Ni(0) toluene and Ni(II) complexes with catalytic application - Ajithkumar, V. S.; Bisai, Milan Kumar; Ghanwat, Pratiksha B.; Raj, K. Vipin; Singh, Geetika; Vanka, Kumar; Sen, Sakya S. (Organometallics, 2025)
The reaction of Ni(COD)2 with [PhC(NtBu)2SiSi(SiMe3)3] (1) in toluene results in the formation of an 18-electron silylene-Ni(0) toluene complex (2). The analogous reaction with 1,3-DFB instead of toluene affords the C-H activation followed by ring walking leading to the allylic cyclooctene adduct, the (eta 3-C8H13)Ni(II) complex (3). DFT calculations were carried out to elucidate the mechanism as well as to gain insight into why 1,3-DFB undergoes C-H bond activation instead of C-F bond activation. The use of NiCl2DME permits access to 16-electron (tetrylene)2NiCl2 (Si(4) and Ge(5)) species, and 4 was later used as a catalyst for the C-N coupling reaction.

Studies on the stereoselective synthesis of sacubitril via a chiral amine transfer approach - Sadanande, Megha V.; Thorat, Sagar S.; Sharma, Himanshu; Singh, Geetika; Vanka, Kumar; Gonnade, Rajesh G.; Kontham, Ravindar (Chemistry-An Asian Journal, 2025)
We present a comprehensive account of our efforts directed towards the synthesis of sacubitril, a neprilysin inhibitor used in combination with valsartan and marketed as Entresto (TM). Our initial approach to the formal synthesis of sacubitril employed a chiral pool strategy, utilizing (S)-pyroglutamic acid as a key building block and Cu(I)-mediated Csp2-Csp3 cross-coupling as a key transformation. Further investigations led to the development of chiral amine transfer (CAT) reagents-based stereoselective synthesis. This involved the E-selective construction of gamma-ylidene-butenolide from readily available biphenyl bromide and 4-pentynoic acid, the conversion of this butenolide to its ene-lactam using chiral amine, and substrate-controlled diastereoselective reduction of ene-lactam using Et3SiH or Pd/C, H2 (overall chiral amine transfer) as key transformations. Antipodal lactam intermediates were synthesized using corresponding chiral amines, and the stereochemical outcomes during the ene-lactam reduction with Et3SiH were rationalized by DFT studies.
Keywords: Chiral Amine Transfer (CAT) approach; Chiral pool approach; Sacubitril; stereoselective synthesis

(NHC-olefin)-nickel(0) nanoparticles: an efficient and selective catalyst for hydrogenation reactions at low temperature and pressure - Avello, Marta G.; Singh, Geetika; Truong-Phuoc, Lai; Vidal, Loic; Papaefthimiou, Vasiliki; Chesse, Matthieu; Gruber, Nathalie; Chetcuti, Michael J.; Vanka, Kumar; Ritleng, Vincent; Pham-Huu, Cuong; Michon, Christophe (Journal of Catalysis, 2026)
The reduction of a NHC-cinnamyl nickel(II) organometallic complex through the use of different MeMgBr or MeMgCl reagents led to two types of NHC-olefin-coordinated nickel nanoparticles. Both of these unsupported nickel-NHC based nanomaterials behaved under hydrogen pressure as effective and selective catalysts operating at low temperature (<= 80 degrees C), pressure (<= 20 bar) and loading (<= 6 mol%) for the reductions of broad scopes of alkenes, alkynes, imines and heterocycles, including a challenging tetra-substituted alkene. Among these two nickel-NHC nanocatalysts, the one generated with MeMgCl showed a significant high catalytic activity with high yields and could stand the comparison with Raney nickel and state-of-the-art nickel nanocatalysts. For example, by studying the hydrogenation of 1-phenylcyclohexene in ethanol at 60 degrees C under 10 bar of H2, 3 mol% of this catalyst achieved the reaction within a single hour on a 5 mmol/0.8 g substrate scale with a yield of 96 %, a turnover number (TON) of 32 and a turnover frequency (TOF) of 32. Characterizations confirmed the coordination of the NHC-olefin ligands to the nickel nanoparticles, the reduced state of the nickel and the (poly-) crystallinity of the nanoparticles.
Keywords: alkenes; Alkynes; heterocycles; Hydrogenation; imines; N -heterocyclic carbene ligand; nanocatalysis; Nickel